A Note on tvs-G-Cone Metric Fixed Point Theory. (10th July 2012) - Lin, Ing-Jer; Chen, Chi-Ming; Chen, Chao-Hung; Cheng, Tien-Ying
Abstract : For a tvs-G -cone metric space( X, G ) and for the family𝒜 of subsets of X, we introduce a new notion of the tvs- ℋ -cone metric ℋ with respect to G, and we get a fixed result for the𝒞 ℬ 𝒲 -tvs-G -cone-type function in a complete tvs-G -cone metric space( 𝒜, ℋ ) . Our results generalize some recent results in the literature.